Huichol mythology - Zingg, Robert M. (Robert Mowry), 1900-1957 (Book collections on Project MUSE., 2004)
"This volume is a collection of myths recorded by Robert Zingg in 1934 in the village of Tuxpan and is the most comprehensive record of Huichol mythology ever published. Zingg was the first professional anthropologist to study the Huichol, and his generosity toward them and political advocacy on their behalf allowed him to overcome tribal sanctions against divulging secrets to outsiders. He is fondly remembered today by some Huichols who were children when he lived among them." "First published in 1998 in a Spanish-language edition, Huichol Mythology is presented here for the first time in English, with more than 40 original photographs by Zingg accompanying the text. For this volume, the editors provide a meticulous historical account of Huichol society from about 200 A.D. through the colonial era, enabling readers to fully grasp the significance of the myths free of the sensationalized interpretations found in popular accounts of the Huichol. Zingg's compilation is a landmark work, indispensable to the study of mythology, Mexican Indians, and comparative religion."--Jacket